Deactivating Cardiac Pacemakers and Implantable Cardioverter Defibrillators in Terminally Ill Patients - Beca, Juan Pablo (Cambridge quarterly of healthcare ethics, 2009)
A 68-year-old patient who suffered from gastric cancer diagnosed 8 months earlier presented with multiple peritoneal and hepatic metastasis, despite several rounds of chemo- and radiotherapy. After admission to hospital, his general condition quickly became severely compromised. He was nearly emaciated, despite being on partial parenteral feeding. Four years earlier, due to a cardiac arrhythmia that was refractory to medication, the patient had a cardiac pacemaker (CPM) implanted, regulated to go off at frequencies of below 70 beats per minute. Given the patient's terminal situation, the team started developing some doubts about the pacemaker's effects during his dying process. The patient had mentioned his intention to donate his pacemaker after his death, but had not asked for its deactivation. The specialists were not sure about the effect of the pacemaker in unnecessarily prolonging the patient's final hour. Nevertheless, they opposed deactivation, which they considered ethically uncertain. The family, who had been initially for the deactivation, decided against it. The patient's condition was progressively deteriorating, as he was falling into a state of sopor and, later, into a coma.